2023
DOI: 10.1111/aas.14291
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory response after out‐of‐hospital cardiac arrest—Impact on outcome and organ failure development

Abstract: BackgroundPost‐cardiac arrest syndrome that occurs in out‐of‐hospital cardiac arrest (OHCA) patients is characterized by inflammatory response. We conducted a scoping review of current evidence regarding several inflammatory markers' usefulness for assessment of patient outcome and illness severity. We also discuss the proposed underlying mechanisms leading to inflammatory response after OHCA.MethodsWe searched the MEDLINE, PubMed Central, Cochrane CENTRAL and Web of Science Core Collection databases with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Myocardial ischemia during cardiac arrest leads to impaired contractility, which is then aggravated through ischemic/reperfusion injury due to an excessive cascade of pro-inflammatory cytokines and elevated circulating catecholamines [ 9 ]. Systemic inflammation contributes to myocardial injury and further to multiorgan dysfunction complicating the clinical status of post-cardiac arrest patients [ 28 , 29 ]. In recent years, two animal studies have found that high-dose glucocorticoid treatment reduced myocardial dysfunction and improved microcirculation in the post-resuscitation phase [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial ischemia during cardiac arrest leads to impaired contractility, which is then aggravated through ischemic/reperfusion injury due to an excessive cascade of pro-inflammatory cytokines and elevated circulating catecholamines [ 9 ]. Systemic inflammation contributes to myocardial injury and further to multiorgan dysfunction complicating the clinical status of post-cardiac arrest patients [ 28 , 29 ]. In recent years, two animal studies have found that high-dose glucocorticoid treatment reduced myocardial dysfunction and improved microcirculation in the post-resuscitation phase [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 17 , 18 , 19 , 38 Further, IFABP has been convincingly associated with mortality after cardiac arrest, while IL-6 are among the few inflammatory biomarkers which are associated with poor outcome after adjustment for confounding factors. 9 , 39 , 40 , 41 , 42 , 43 , 44 Importantly, IFABP and inflammatory biomarkers could merely increase in parallel with the degree of whole-body ischaemia. 20 , 21 …”
Section: Discussionmentioning
confidence: 99%